When should we expect microbial phenotypic traits to predict microbial abundances? - Fox, Jeremy W. (Frontiers in Microbiology, 2012)
Species’ phenotypic traits may predict their relative abundances. Intuitively, this is because locally-abundant species have traits making them well adapted to local abiotic and biotic conditions, while locally-rare species are not as well-adapted. But this intuition may not be valid. If competing species vary in how well-adapted they are to local conditions, why doesn’t the best-adapted species simply exclude the others entirely? But conversely, if species exhibit niche differences that allow them to coexist, then by definition there is no single best adapted species. Rather, demographic rates depend on species’ relative abundances, so that phenotypic traits conferring high adaptedness do not necessarily confer high abundance. I illustrate these points using a simple theoretical model incorporating adjustable levels of "adaptedness" and "niche differences". Even very small niche differences can weaken or even reverse the expected correlation between adaptive traits and abundance. Conversely, adaptive traits confer high abundance when niche differences are very strong. Future work should be directed towards understanding the link between phenotypic traits and frequency-dependence of demographic rates.